Photos of Old Watkins Family Photographs - Watkins, Howard::::::::: (1988)
Albert Watkins, Florence Watkins, Aaron "Jack" Watkins, Raymond Watkins, and Jack's wife, Hazel May Culp Watkins-1942 In front of family car at 207 Geneva Avenue, Huntington Beach